Implementation of ATP and History Teaching Modules in the Merdeka Curriculum at SMA Negeri 1 Rogojampi - Nur Hikayah; Saskia Wulandari; Nurul Lutfiyana Rizky; Diki Wahyu Saputra (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The implementation of the Merdeka Curriculum requires teachers to design flexible and meaningful learning plans that support student-centered learning and the development of higher-order thinking skills, particularly in history education. This study aims to describe the implementation of the Learning Objective Flow (Alur Tujuan Pembelajaran/ATP) and history teaching modules based on the Merdeka Curriculum at SMA Negeri 1 Rogojampi, as well as to identify challenges encountered in their application. This research employed a qualitative descriptive approach, with data collected through classroom observations, interviews with history teachers, and documentation analysis of ATP documents and teaching modules. The results indicate that ATP is implemented in a structured yet flexible manner, functioning as a practical guide for organizing learning objectives, sequencing materials, and adapting instructional strategies to students’ characteristics, while teaching modules support differentiated learning, authentic assessment, and the integration of digital media. In conclusion, the implementation of ATP and teaching modules reflects the core principles of the Merdeka Curriculum by promoting adaptive, contextual, and student-centered history learning, although challenges remain in developing higher-order thinking skills (HOTS) assessments and strengthening teacher collaboration.